Buying & selling a business : - Klueger, Robert F. (John Wiley & Sons, Inc., 2004)
For more than fifteen years, this handy guide has provided entrepreneurs and small business owners with a simple, step-by-step plan for buying or selling a business–without their own special team of lawyers and accountants. Written by leading business attorney Robert Klueger, this up-to-date guide now includes everything you need to know about recent tax law changes, as well as an entirely new chapter on limited liability companies. It answers all your critical questions, covering everything from the valuation of a business through the negotiation stages to closing the deal. Packed with the kind of real-world guidance you can only get from a professional, Buying & Selling a Business, Second Edition shows you how to: Choose a business that’s right for you; Evaluate the business, determine why the seller is selling, analyze the seller's operations, and analyze balance sheets, income statements, and cash flow; Negotiate effectively–including negotiating for price, timing, stock and asset agreements, noncompetitive agreements, and more; Buy a franchise–key considerations that make a franchise different; Ensure a hassle-free closing with no surprises.